ECONOMIC PRACTICES OF ‘MAMA-MAMA PAPUA’ USING SHIFTING CULTIVATION SYSTEM: STUDY CASE IN SORONG AND MAYBRAT REGENCIES - WESTERN PAPUA - Kadir, Hatib Abdul; Mahadika, Gilang (Jurnal Perempuan, 2019)
This research examines women?s role and their decision-making related to swidden farming. This research was conducted in two different regions, Sorong (lowland) and Maybrat (highland) in West Papua. Key informants in this research were indigenous Papuan women, their husbands, and relatives. The aim of the research is to demonstrate that in the realm of traditional agriculture, women play important roles, starting from production, plant nursery, to the crop distribution to market. Nonetheless, the role of women tends to disappear, when the system of agriculture changes to sedentary farming by using chemical substances and other modern and farming technologies.